Hyers–Ulam–Mittag-Leffler Stability for a System of Fractional Neutral Differential Equations. (21st May 2020) - Ahmad, Manzoor; Jiang, Jiqiang; Zada, Akbar; Ali, Zeeshan; Fu, Zhengqing; Xu, Jiafa
Abstract : This article concerns with the existence and uniqueness for a new model of implicit coupled system of neutral fractional differential equations involving Caputo fractional derivatives with respect to the Chebyshev norm. In addition, we prove the Hyers–Ulam–Mittag-Leffler stability for the considered system through the Picard operator. For application of the theory, we add an example at the end. The obtained results can be extended for the Bielecki norm.